Investigation of the phase formation and dielectric properties of Bi7Ta3O18 - Chon, Mun Ping; Tan, Kar Ban; Khaw, Chwin Chieh; Zainal, Zulkarnain; Yap, Taufiq Yun Hin; Chen, Soo Kien; Tan, Phei Yi (Elsevier, 2014)
Polycrystalline Bi7Ta3O18 was synthesised at the firing temperature of 950 °C over 18 h via conventional solid state method. It crystallised in a monoclinic system with space group C2/m, Z = 4 similar to that reported diffraction pattern in the Inorganic Crystal Structure Database (ICSD), 1-89-6647. The refined lattice parameters were a = 34.060 (3) Å, b = 7.618 (9) Å, c = 6.647 (6) Å with α = γ = 90° and β = 109.210 (7), respectively. The intermediate phase was predominantly in high-symmetry cubic structure below 800 °C and finally evolved into a low-symmetry monoclinic structured, Bi7Ta3O18 at 950 °C. The sample contained grains of various shapes with different orientations in the size ranging from 0.33–22.70 μm. The elemental analysis showed the sample had correct stoichiometry with negligible Bi2O3 loss. Bi7Ta3O18 was thermally stable and it exhibited a relatively high relative permittivity, 241 and low dielectric loss, 0.004 at room temperature, ∼30 °C and frequency of 1 MHz.